PDE accident model from a safety information perspective and its application to Zhangjiakou fire and explosion accident. (November 2020) - Wang, Bing; Zhu, Zhaozhen; Wu, Chao; Zhang, HongJian; Liao, Xiuping
Abstract: Accident models can provide theoretical frameworks for determining the causes and mechanisms of accidents, and thus are theoretical bases for accident analysis and prevention. The role of safety information in accident causation is profound. Thus, safety information is an important and essential perspective for developing accident models. This study presents a new accident model developed from a safety information perspective, called the Prediction—Decision—Execution (PDE) accident model. Because the PDE accident model is an emerging accident model that was proposed in 2018, its analysis logic and viability remain to be discussed. Thus, the main contributions of this study include two aspects: (i) detailed explanation of the analysis logic of the PDE accident model, and (ii) case-study examination of the Zhangjiakou fire and explosion accident, a serious accident that occurred in China in 2018, to demonstrate the viability of the PDE accident model. Results show that this is a safety-information-driven accident model that can provide a new and effective methodology for accident analysis and prevention, and safety management. Highlights: The PDE accident model was introduced. The analysis logic of the PDE accident model was discussed. The PDE accident model was applied to the analysis of Zhangjiakou fire and explosion accident.